Psychophysiological wellbeing in a class of dental students attending dental school: anxiety, burnout, post work executive performance and a 24 hours physiological investigation during a working day - Queirolo, Luca; Roccon, Andrea; Piovan, Silvia; Ludovichetti, Francesco Saverio; Bacci, Christian; Zanette, Gastone (Frontiers in Psychology, 2024)
Aim: To our knowledge dDental school students have never been evaluated for stress, anxiety, burnout, physiological indexes during a 24-hour working day, and executive functions performancece postwork and post-work after returning from vacation,, therefore this research has been conducted. Methods: Data were acquired at the Dental School of the University of Padua on 16 students in their 4 th year, far from the exam's session. while performing clinical activity on the dental chair and during a working day. Electrodermal activity (EDA), heart rate variability (HRV), and Heart rate (HR) were recorded. Participants' stress was measured with the Perceived Stress Scale (PSS-10 scale), anxiety with the General Anxiety Disorder Questionnaire (GAD-7) and State-Trait Anxiety Inventory (STAI-Y-2), while Burnout with the Maslach Burnout Inventory (MBI-HSS). Executive functions were evaluated with the Tower of London test (TOL-R).Results: Three students (2F/1M) had a GAD-7 score ≥ 10. Five students (4F/1M) showed trait anxiety. 85% of participants reported moderate levels of perceived stress. MBI-HSS showed 7 participants scored high on Emotional exhaustion and 7 on Depersonalization. TOL-R performance (M=15.85, SD= 4.01) was below the normative value p<0.00001. A second test, after holidays, showed normal values. EDA was higher during children treatment (p<0.05), ANOVA showed high HR during working time (p<0.001), and HRV was higher in males (p<0.001).Based on the sample size evaluated it is reported that bBeing a dental student has a moderate impact on stress, anxiety, and burnout while a strong impact on executive functions buffered by rest., .As the reviewer asked we changed from introduction to aim and we used a softer approach to the "have never been evaluated before" Formattato: Allineato a sinistra ha formattato: Apice